CAPITAL AND REVENUE EXPENDITURES. - Avery, Harold G. (The Accounting Review, 1941)
Abstract Business management must establish policies to distinguish between capital and revenue expenditures in order to maintain and successfully operate an accounting system, which provides for the classification and control of depreciable fixed assets. Certain standards must be devised by accounting or engineering department in order to separate capital from expense items. The adoption of such policies and standards is more important now than ever before because of management problems involved in fulfilling defense contracts. Accurate costs have to be determined whether or not the type of governmental supply contract is described as a fixed-price, cost-plus-a-fixed-fee, or cost-plus-a-percentage-of-cost contract. Emergency facilities, including land, buildings, machinery and equipment, used for the purpose of completing a defense contract can be amortized over a period of 60 months if certain government regulations and requirements ate followed. Therefore, it becomes necessary for the management to distinguish carefully between costs coming under a supply contract and costs involved in capital expansion.